Sexual Violence on Women in the View of Legal and Human Rights in Indonesia - Andi LALA; Eman SUPARMAN; Amin PURNAWAN; Abdullah ABDULLAH (International Journal of Environmental, Sustainability, and Social Science, 2023)
Sexual violence is a term that refers to derivative sexual behavior or relationships that are distorted, harming the victim and destroying peace in society, for example, cases of sexual violence that occur to women (including girls) are carried out by those closest to them. Based on the fact sheets in the 2020 Komnas Perempuan Annual Records, sexual violence was perpetrated by 1,528 boyfriends, 425 biological fathers, 322 uncles, 205 stepfathers, 192 husbands, 89 siblings, and 58 biological grandfathers. This research is a normative legal research. One form of violence against women is sexual violence. From the available data it appears that sexual violence in places against women is as much as non-sexual violence. In our country's Criminal Code it only includes articles on rape or obscenity, this is what is then from a human rights perspective, the position of women's human rights feels humiliated and even abused, while human rights issues in our country already have rules that regulate and even guarantee human rights guarantees for everyone. namely Law Number 39 of 1999 concerning Human Rights